Measuring financial risk in non-financial firms: an application to the Colombian sugar sector (2015)
(Eng) Investment projects optimal selection is relevant in making business decisions. In this paper a methodology that has not been extensively explored in the literature of measuring financial risk is applied to the Colombian sugar industry. This measurement serves as the basis for the evaluation of projects in a more robust manner, due to an adequate modeling of uncertainty. For the above, the Value at Risk of a company’s gross profit is determined using econometric techniques such as modeling the autoregressive conditional volatility of the series, multivariate modeling of the dependency relationships of the series through copulas, and simulation using Monte Carlo techniques.